2021
DOI: 10.3389/fcomp.2021.546960
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Pulmonary Rehabilitation: Feasibility of Delivery by a Mobile Phone-Based Program

Abstract: Background: Pulmonary rehabilitation (PR) has been proven effective but is not well accessed due to transport, time, cost, and physical limitations of patients. We have developed a mobile phone-based PR program (mPR) that could be offered as an alternative for those unable to attend in-person. This was developed following formative research with patients, their families and clinicians. mPR has a core text message program plus an app that includes an action plan, exercise videos, lung visualization, symptom sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…9,10 A mHealth PR programme (mPR) was developed in 2019 for use in Aotearoa New Zealand (NZ) context by our team of public health and mHealth experts, physiotherapists, respiratory physicians, psychologists, respiratory nurse specialists, cultural experts, and ongoing input from end users. 11,12 The feasibility of this programme has been demonstrated for people living with CRD in NZ. 12 Patients have preferences for how they receive rehabilitation programmes; 13,14 however, an important limitation in PR clinical trials to date is that they do not account for patient preferences for mode of delivery [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,10 A mHealth PR programme (mPR) was developed in 2019 for use in Aotearoa New Zealand (NZ) context by our team of public health and mHealth experts, physiotherapists, respiratory physicians, psychologists, respiratory nurse specialists, cultural experts, and ongoing input from end users. 11,12 The feasibility of this programme has been demonstrated for people living with CRD in NZ. 12 Patients have preferences for how they receive rehabilitation programmes; 13,14 however, an important limitation in PR clinical trials to date is that they do not account for patient preferences for mode of delivery [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The feasibility of this programme has been demonstrated for people living with CRD in NZ. 12 Patients have preferences for how they receive rehabilitation programmes; 13,14 however, an important limitation in PR clinical trials to date is that they do not account for patient preferences for mode of delivery [13][14][15][16] . Several home-based trials of PR have reported low uptake due to participant's preference for centre-based PR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary rehabilitation is a comprehensive therapeutic intervention for patients with respiratory disorders, 3 which is effective in improving their quality of life. 4 Pulmonary rehabilitation is defined as “a comprehensive intervention based on a thorough patient assessment followed by patient‐tailored therapies that include but are not limited to, exercise training, education, and behavior change designed to improve the physical and psychological condition of people with chronic respiratory disease and promote the long‐term adherence to health‐enhancing behaviors.” 5 The benefits of pulmonary rehabilitation do not last over time and gradually disappear between 6 and 12 months after the end of pulmonary rehabilitation. Lack of commitment to rehabilitation seems to be one of the possible reasons for losing these benefits.…”
Section: Introductionmentioning
confidence: 99%